Classification of smooth muscle autoantibodies detected by immunofluorescence. Issue 5 (May 1976) - Bottazzo, G F; Florin-Christensen, A; Fairfax, A; Swana, G; Doniach, D; Groeschel-Stewart, U
Abstract : Three hundred and twelve sera containing antibodies to smooth muscle (SMA) wer analysed for the immunofluorescence patterns they produced in various tissues. A classification is described based on the three main appearances in rat kidney. Some sera, mainly of low titre, reacted only with vessel walls (SMA-V), some stained vessels and renal glomeruli (SMA-G) and high titre sera, mainly from patients with chronic active hepatitis stained vessels, glomeruli, and intracellular fibrils in renal tubules (SMA-T). Peripheral staining in hepatocytes or thyroid cells was not a regular feature. 41/43 polyclonal SMA-T and -G sera were absorbed out completely by actin, and this also removed the pericullular staining in liver and thyroid when present. High titre SMA-V antibodies could not be absorbed by actin, and the antigen remains to be identified.